Call for Papers: The New Landscape of Public Administration - Trends, Challenges, and Future Pathways - Berlin, Johan; Bretzer, Ylva Norén; Brorström, Björn; Fırtın, Cemil Eren; Johansson, Vicki; Zapata, Patrik (Scandinavian Journal of Public Administration, 2025)
Building on its legacy under previous titles –Kommunal Ekonomi och Politik (1997–2009) and Offentlig Förvaltning: Scandinavian Journal of Public Administration (2010–2013)– the Scandinavian Journal of Public Administration (SJPA) has, over the past three decades, established itself as a central platform for scholars and practitioners engaged in the study of public administration across Scandinavia. As we mark the 30th anniversary of the journal, this special issue offers an opportunity to reflect on past contributions while charting out future directions in public sector research. Since its inception, SJPA has documented key developments in governance, from the rise of New Public Management (NPM) and market-driven reforms in the 1990s to current debates on digitalization, sustainability, and collaborative governance.